Composite PE film based on modified graphene and preparation method thereof

Through the combination of modified graphene and polyvinyl matrix, the combination of modified resin and modified graphene is used to solve the problem of insufficient performance of PE films in high-end applications, and the waterproof, corrosion resistance and aging resistance of composite PE films have been significantly improved, with excellent application prospects.

CN119823468AInactive Publication Date: 2025-04-15DONGGUAN TIANJIA IND CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510036944.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-04-15
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In high-end applications, existing PE films have problems such as low thermal conductivity, limited waterproof and weathering performance and insufficient mechanical strength, especially in extreme environments, the long-term stability and reliability of materials are difficult to guarantee.

Method used

Modified graphene is combined with polyvinyl matrix, and the waterproof, corrosion resistance and aging resistance of the composite PE film are improved by combining the modified resin and the modified graphene, and the aggregation ability of oxidized molecules is enhanced through the special structure of the modified graphene, and the mechanical properties of the material are improved.

Benefits of technology

It significantly improves the waterproof, corrosion resistance and aging resistance of composite PE films, avoids the problem of degradation of mechanical and mechanical properties, has outstanding use effect, and has excellent and broad application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005235796230000141
    Figure BDA0005235796230000141
Patent Text Reader

Abstract

The invention relates to the field of membrane materials, in particular to a composite PE membrane based on modified graphene and a preparation method of the composite PE membrane. The composite PE film based on modified graphene is prepared from the following raw materials in parts by mass: 50-70 parts of a polyethylene matrix, 10-20 parts of modified resin, 5-10 parts of modified graphene, 1-1.5 parts of an antioxidant, 0.8-1.4 parts of a stabilizer, 4-8 parts of a plasticizer, 0.5-1 part of a lubricant, 2-4 parts of a nucleating agent, 1-3 parts of a bonding aid and 10-15 parts of a dispersing solvent. The composite PE film prepared by the invention not only can effectively exert the functionality of graphene, but also can effectively and simultaneously improve the properties such as waterproofness, corrosion resistance, weather resistance, aging resistance and the like, avoids the problem that the mechanical properties of the existing graphene PE composite film are easy to reduce, has an outstanding use effect, and is suitable for popularization and application. And the method has very excellent and wide application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of membrane materials, and in particular to a composite PE membrane based on modified graphene and a preparation method thereof. Background Art

[0002] With the development of science and technology and the increase of social needs, the demand for high-performance composite materials is also growing. Traditional polyethylene (PE) film has been widely used in many fields due to its excellent processing performance, low cost and good mechanical properties. However, ordinary PE film has limitations in some high-end applications, such as low thermal conductivity, limited waterproof and weather resistance, and relatively insufficient mechanical strength, which limits its application scope in certain specific fields.

[0003] In recent years, graphene, as a new type of two-dimensional nanomaterial, has attracted widespread attention due to its unique physical and chemical properties. Graphene has an extremely high specific surface area, excellent electrical and thermal conductivity, excellent mechanical properties and good optical transparency. By introducing graphene into a polymer matrix to form a composite material, the comprehensive properties of the original polymer material can be significantly improved.

[0004] However, for existing PE films, there is a lack of sufficient chemical affinity between graphene and PE, resulting in weak interface bonding between the two, limiting the effective transfer of stress, and thus affecting the mechanical, waterproof, corrosion and aging resistance of the composite material. Therefore, the overall performance improvement effect of the composite PE film may not achieve the expected goal, especially when used under extreme environmental conditions, the long-term stability and reliability of the material are difficult to guarantee.

[0005] Therefore, in order to effectively solve the above problems, the present application provides a composite PE film based on modified graphene and a preparation method thereof. The composite PE film prepared in the present application can not only effectively exert the functionality of graphene, but also effectively improve its own waterproof, corrosion-resistant, weather-resistant and aging-resistant properties, and avoid the problem of mechanical properties degradation that is easy to occur in existing graphene PE composite films. The use effect is outstanding and has a very excellent and broad application prospect. Summary of the invention

[0006] In order to solve the above problems, the first aspect of the present application provides a composite PE film based on modified graphene. The raw materials are, by mass: 50 to 70 parts of polyethylene matrix, 10 to 20 parts of modified resin, 5 to 10 parts of modified graphene, 1 to 1.5 parts of antioxidant, 0.8 to 1.4 parts of stabilizer, 4 to 8 parts of plasticizer, 0.5 to 1 part of lubricant, 2 to 4 parts of nucleating agent, 1 to 3 parts of bonding agent, and 10 to 15 parts of dispersing solvent.

[0007] As a preferred solution, the polyethylene matrix is ​​a composition of high-density polyethylene and linear low-density polyethylene.

[0008] As a preferred solution, the mass ratio of the high-density polyethylene to the linear low-density polyethylene is (40-48):(12-20).

[0009] As a preferred solution, the mass ratio of the high-density polyethylene to the linear low-density polyethylene is 45:15.

[0010] As a preferred solution, the melt flow rate of the linear low-density polyethylene is 3.5-4.5 g / 10 min, and the temperature condition is 190°C.

[0011] As a preferred solution, the mass ratio of the polyethylene matrix, the modified resin and the modified graphene is (55-65): (12-16): (6-9).

[0012] As a preferred solution, the mass ratio of the polyethylene matrix, the modified resin and the modified graphene is 60:14:7.5.

[0013] As a preferred solution, the mass ratio of the modified graphene, the nucleating agent and the bonding aid is (6-9): (2.5-3): (1.5-2).

[0014] As a preferred solution, the mass ratio of the modified graphene, the nucleating agent and the bonding aid is 7.5:2.5:1.8.

[0015] As a preferred solution, the preparation method of the modified resin specifically includes the following steps: S1: After polybutylene succinate diol and polycarbonate diol are stirred and mixed uniformly at 50-55°C and 200-240rpm in a high-speed mixer, the mixture is taken out, added to a reaction container, heated to 80-85°C, diphenylmethane diisocyanate and dibutyltin dilaurate are added, and the reaction is kept warm for 4-4.5h to obtain a prepolymer; S2: The prepolymer, glycidyl methacrylate, trimethylolpropane triacrylate, N,N'-ethylenebisacrylamide and N,N'-isophthalenebisacrylamide are mixed, the temperature is raised to 100-120°C, potassium persulfate is added, and the reaction is kept warm for 6-8h; S3: After the reaction is completed, the temperature is naturally cooled to room temperature, the product is sieved through a 400-450 mesh sieve to remove large particles, and then kept warm overnight. After completion, it is sealed and stored to obtain.

[0016] As a preferred solution, the mass ratio of the polybutylene succinate diol, polycarbonate diol and diphenylmethane diisocyanate is (4-5): (1-2): (6-8).

[0017] As a preferred solution, the mass ratio of the precursor, glycidyl methacrylate, trimethylolpropane triacrylate, N,N'-ethylenebisacrylamide and N,N'-isophthalenebisacrylamide is (4-6):(10-12):(0.2-0.3):(1-1.5):(0.4-0.6).

[0018] As a preferred solution, the preparation method of the modified graphene specifically comprises the following steps: S1: adding the functionalized graphene and zinc oxide to a DMF solution, then adding succinic anhydride and heating to 65-70°C, keeping the temperature for reaction for 2.5-3h, centrifuging and filtering the product after completion, and drying to obtain pretreated solid particles; S2: ultrasonicating the pretreated solid particles in a DMAc solvent at 400-500W in a water bath for 40-60min, adding tetrabutyl titanate after completion, and then heating to Keep warm at 50-55℃ and perform ultrasonic treatment for 20-30min, then add 1,4-naphthalene dicarboxylic acid, p-aminobenzoic acid and 2-methylimidazole, raise the temperature to 90-100℃ and keep warm for 4-5h; S3: add hydrofluoric acid, stir and mix evenly, raise the temperature to 110-125℃ and stir at 80-100rpm for reaction for 14-16h. After the reaction is completed, cool naturally to room temperature, centrifuge and filter, wash with ethanol 2-3 times and dry in a vacuum drying oven at 80-85℃ for 6-8h to obtain.

[0019] As a preferred solution, the mass ratio of the functionalized graphene, zinc oxide and succinic anhydride is (4-4.5): (0.4-0.6): (1.2-1.5).

[0020] As a preferred solution, the mass ratio of the pretreated solid particles, tetrabutyl titanate, 1,4-naphthalene dicarboxylic acid, p-aminobenzoic acid and 2-methylimidazole is (5-5.5): (2.2-2.4): (2-2.2): (0.4-0.6): (0.2-0.3).

[0021] As a preferred solution, the average particle size of the zinc oxide is 10 to 20 nm.

[0022] As a preferred solution, the antioxidant is at least one of antioxidant 1010, antioxidant 1076, antioxidant B215, antioxidant 168, antioxidant CA and antioxidant 1098.

[0023] As a preferred solution, the antioxidant is antioxidant 168.

[0024] As a preferred solution, the stabilizer is at least one of Tinuvin 328, Tinuvin 234, Tinuvin 123 and Tinuvin 1577.

[0025] As a preferred solution, the stabilizer is Tinuvin 328.

[0026] As a preferred solution, the plasticizer is a combination of dioctyl adipate and epoxidized soybean oil.

[0027] As a preferred solution, the mass ratio of dioctyl adipate to epoxidized soybean oil is (3-5):(1.5-2).

[0028] As a preferred solution, the lubricant is at least one of calcium stearate, zinc stearate, polyethylene wax, ethylene bisstearamide and silicone oil.

[0029] As a preferred solution, the lubricant is ethylene bisstearamide.

[0030] As a preferred solution, the nucleating agent is at least one of organic montmorillonite, sorbitol, talcum powder, calcium carbonate and barium sulfate.

[0031] As a preferred solution, the nucleating agent is barium sulfate.

[0032] As a preferred solution, the barium sulfate is ultrafine barium sulfate with an average particle size of 0.5 to 1 μm.

[0033] As a preferred solution, the bonding aid is a composition of maleic anhydride grafted polyethylene and γ-aminopropyltriethoxysilane.

[0034] As a preferred solution, the mass ratio of the maleic anhydride grafted polyethylene to γ-aminopropyltriethoxysilane is (4-5): (0.5-1).

[0035] As a preferred solution, the dispersing solvent is at least one of NMP, NMP or IPA.

[0036] The second aspect of the present application provides a method for preparing the above-mentioned composite PE film based on modified graphene, which specifically includes the following steps: S1: adding the modified graphene to a dispersing solvent, and dispersing it in a water bath ultrasonic manner at 400-500W for 60-90min until there is no agglomeration, to obtain a modified graphene dispersion; S2: pre-mixing the modified resin, antioxidant, stabilizer, plasticizer, lubricant, nucleating agent and adhesive additive under stirring at a speed of 120-200rpm, then adding the mixture of the polyethylene matrix and the modified graphene dispersion, and stirring at a speed of 80-100rpm until uniform to obtain a blend; S3: sending the blend into a twin-screw extruder for melt blending, the screw speed is 300-400rpm, the temperature gradient is controlled between 160-200℃, to ensure that the material is fully plasticized but not degraded, the extruded melt is formed into a film by a film blowing machine, the blowing ratio is adjusted to (2-3):1, and the film is pulled to the required film thickness and flatness, and then cooled and shaped to complete.

[0037] The beneficial effects of this application are:

[0038] 1. The composite PE film based on modified graphene provided in the present application can not only effectively exert the functionality of graphene, but also effectively improve its own waterproof, corrosion-resistant, weather-resistant and aging-resistant properties at the same time, and avoid the problem of mechanical properties degradation that is easy to occur in existing graphene PE composite films. The use effect is outstanding and has a very excellent and broad application prospect.

[0039] 2. A composite PE film based on modified graphene provided in the present application can provide activity space for the relative movement of molecular chains in the rigid segments by introducing soft segment molecular chains through the added modified resin, and can provide good stress dissipation effect through the flexible movement of soft segments under strong external forces, thereby enhancing mechanical properties; on the other hand, the addition of modified resin can improve the mutual adhesion between molecular segments in the system and improve the regularity of the three-dimensional cross-linked network, thereby greatly reducing the microcracks and continuous particle voids caused by molecular chain slippage, thereby maintaining the system's barrier ability for water molecules and active molecules, reducing their penetration into the PE film, and thereby obtaining good waterproof, corrosion-resistant, aging-resistant and weather-resistant properties.

[0040] 3. A composite PE film based on modified graphene provided in the present application can achieve a barrier effect on water molecules through the special structure of planar multiple active sites formed by the added modified graphene, thereby limiting the formation of a continuous hydration layer on the surface of the PE film and the penetration of active molecules, thereby achieving good waterproof, aging and corrosion resistance and other properties; and at the same time, the special structure formed by it greatly enhances the aggregation of oxidized molecules on the surface, thereby effectively oxidizing surface organic matter, thereby obtaining good corrosion resistance and weather resistance of the PE film. DETAILED DESCRIPTION

[0041] The following will further explain and demonstrate the technical solutions in the above invention content of this application in the form of specific implementation schemes. The following embodiments are only practical examples used to illustrate and explain the contents of the technical solutions in the specification, and should not limit the scope of the claims to be protected by this application. All technical products based on the technical solutions described in the invention content of this application should be included in the scope to be protected by this application.

[0042] In the following examples, unless otherwise specified, the raw materials are all commercially available products, or can be prepared by methods well known to those skilled in the art.

[0043] Example 1

[0044] Example 1 The first aspect provides a composite PE film based on modified graphene. The raw materials are, by mass, 60 parts of polyethylene matrix, 14 parts of modified resin, 7.5 parts of modified graphene, 1.2 parts of antioxidant, 0.9 parts of stabilizer, 4.4 parts of plasticizer, 0.8 parts of lubricant, 2.5 parts of nucleating agent, 1.8 parts of bonding aid, and 12.5 parts of dispersing solvent.

[0045] The polyethylene matrix is ​​a composition of high-density polyethylene and linear low-density polyethylene, and the mass ratio of the two is 45:15.

[0046] High-density polyethylene was purchased from BE0400 model product sold by LG Company of South Korea.

[0047] The linear low-density polyethylene has a melt flow rate of 4.2 g / 10 min, and the temperature condition is 190° C. The product is model 41E719 purchased from Dow Chemical Company of the United States.

[0048] The preparation method of the modified resin specifically comprises the following steps, calculated by mass: S1: 4.6 parts of polybutylene succinate diol and 1.5 parts of polycarbonate diol are stirred and mixed uniformly in a high-speed mixer at 55° C. and 200 rpm, the mixture is taken out, added to a reaction container, heated to 85° C., 7.4 parts of diphenylmethane diisocyanate and 0.11 parts of dibutyltin dilaurate are added, and the reaction is kept warm for 4.5 hours to obtain a prepolymer; S2: 5 .5 parts of the precursor, 11.2 parts of glycidyl methacrylate, 0.24 parts of trimethylolpropane triacrylate, 1.4 parts of N,N'-ethylenebisacrylamide and 0.5 parts of N,N'-isophthalenebisacrylamide are mixed, the temperature is raised to 110°C, potassium persulfate is added and the reaction is kept warm for 7.5 hours; S3: After the reaction is completed, the temperature is naturally cooled to room temperature, the product is sieved through a 420-mesh sieve to remove large particles, and then kept warm overnight. After completion, it is sealed and stored to obtain the product.

[0049] Polybutylene Succinate Diol is an industrial premium grade product sold by Hubei Langbowan Co., Ltd., China.

[0050] Polycarbonate diol was purchased as an industrial grade product sold by Guangdong Wengjiang Chemical Reagent Co., Ltd., China.

[0051] The preparation method of modified graphene specifically includes the following steps, calculated by mass: S1: 4.2 parts of functionalized graphene and 0.55 parts of zinc oxide are mixed and added to 80 parts of DMF solution, and then 1.4 parts of succinic anhydride are added and the temperature is raised to 70°C, and the reaction is kept warm for 3 hours. After completion, the product is centrifuged and filtered, and the pretreated solid particles are obtained after drying; S2: 5.3 parts of the pretreated solid particles are ultrasonically treated in 120 parts of DMAc solvent at 400W for 50 minutes, and after completion, 2.3 parts of tetratitanate are added S3: add 0.3 parts of hydrofluoric acid, stir and mix evenly, heat to 120°C and stir at 100 rpm for 15 hours. After the reaction is completed, cool naturally to room temperature, centrifuge and filter, wash 3 times with ethanol and dry in a vacuum drying oven at 80°C for 8 hours.

[0052] Functionalized graphene was purchased from Jiangxi Shuobang New Material Technology Co., Ltd., China, and the surface hydroxyl / carboxyl functionalized graphene products had an average diameter of 0.9 μm.

[0053] The average particle size of zinc oxide is 16 nm.

[0054] The antioxidant is antioxidant 168; the stabilizer is Tinuvin 328; the plasticizer is a combination of dioctyl adipate and epoxidized soybean oil, the mass ratio of the two is 4:1.8, and the epoxidized soybean oil is purchased from Shandong Yueyang New Materials Co., Ltd. in China as a premium product.

[0055] The lubricant is ethylene bis stearamide; the nucleating agent is ultrafine barium sulfate with an average particle size of 0.7 μm.

[0056] The adhesive aid is a composition of maleic anhydride grafted polyethylene and γ-aminopropyltriethoxysilane, with a mass ratio of 4.5:0.8; the maleic anhydride grafted polyethylene was purchased from the ZJ-900E model product sold by Wuhan Huaxiang Kejie Biotechnology Co., Ltd. in China.

[0057] The dispersion solvent was NMP.

[0058] The second aspect of the present embodiment provides a method for preparing the above-mentioned composite PE film based on modified graphene, which specifically includes the following steps: S1: adding the modified graphene to a dispersing solvent, and dispersing it in a 450W water bath ultrasonic manner for 80 minutes until there is no agglomeration, to obtain a modified graphene dispersion; S2: pre-mixing the modified resin, antioxidant, stabilizer, plasticizer, lubricant, nucleating agent and adhesive additive under stirring at a speed of 180rpm, and then adding the mixture of polyethylene matrix and modified graphene dispersion, stirring at a speed of 100rpm until uniform, to obtain a blend; S3: sending the blend into a twin-screw extruder for melt blending, the screw speed is 400rpm, and the temperature gradient is controlled between 180 and 200°C to ensure that the material is fully plasticized but not degraded. The extruded melt is formed into a film by a film blowing machine, the blowing ratio is adjusted to 2.5:1, and the film is pulled to the required film thickness and flatness, and then cooled and shaped to complete.

[0059] Example 2

[0060] The specific implementation of this embodiment is basically the same as that of Example 1, with the only difference being that the raw materials of the composite PE film based on modified graphene, in parts by mass, are: 65 parts of polyethylene matrix, 12 parts of modified resin, 6 parts of modified graphene, 1.2 parts of antioxidant, 0.9 parts of stabilizer, 4.4 parts of plasticizer, 0.8 parts of lubricant, 3 parts of nucleating agent, 1.5 parts of bonding agent, and 12.5 parts of dispersing solvent.

[0061] The polyethylene matrix is ​​a composition of high-density polyethylene and linear low-density polyethylene, and the mass ratio of the two is 45:20.

[0062] The adhesive auxiliary agent is a composition of maleic anhydride grafted polyethylene and gamma-aminopropyltriethoxysilane, and the mass ratio of the two is 5:1.

[0063] Example 3

[0064] The specific implementation of this embodiment is basically the same as that of Example 1, with the only difference being that the raw materials of the composite PE film based on modified graphene, in parts by mass, are: 55 parts of polyethylene matrix, 16 parts of modified resin, 9 parts of modified graphene, 1.2 parts of antioxidant, 0.9 parts of stabilizer, 4.4 parts of plasticizer, 0.8 parts of lubricant, 2.5 parts of nucleating agent, 2 parts of bonding aid, and 12.5 parts of dispersing solvent.

[0065] The polyethylene matrix is ​​a composition of high-density polyethylene and linear low-density polyethylene, and the mass ratio of the two is 40:15.

[0066] The adhesive auxiliary agent is a composition of maleic anhydride grafted polyethylene and gamma-aminopropyltriethoxysilane, and the mass ratio of the two is 4:1.

[0067] Comparative Example 1

[0068] The specific implementation of this comparative example is basically the same as that of Example 1, with the only difference being: 65 parts of polyethylene matrix, 5.2 parts of modified resin, 10.5 parts of modified graphene, 1.2 parts of antioxidant, 0.9 parts of stabilizer, 4.4 parts of plasticizer, 0.8 parts of lubricant, 2.5 parts of nucleating agent, 1.8 parts of bonding aid, and 12.5 parts of dispersing solvent.

[0069] Comparative Example 2

[0070] The specific implementation of this comparative example is basically the same as that of Example 1, with the only difference being: 70 parts of polyethylene matrix, 22.5 parts of modified resin, 2.5 parts of modified graphene, 1.2 parts of antioxidant, 0.9 parts of stabilizer, 4.4 parts of plasticizer, 0.8 parts of lubricant, 2.5 parts of nucleating agent, 1.8 parts of bonding aid, and 12.5 parts of dispersing solvent.

[0071] Comparative Example 3

[0072] The specific implementation of this comparative example is basically the same as that of Example 1, except that the polyethylene matrix is ​​a composition of high-density polyethylene and linear low-density polyethylene, and the mass ratio of the two is 60:5.

[0073] Comparative Example 4

[0074] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of the modified resin specifically comprises the following steps, calculated by mass: S1: After 6.5 parts of polycarbonate diol are stirred and mixed uniformly in a high-speed mixer at 55°C and 200 rpm, the mixture is taken out, added to a reaction container, heated to 85°C, 7.4 parts of diphenylmethane diisocyanate and 0.11 parts of dibutyltin dilaurate are added, and the reaction is kept warm for 4.5 hours to obtain a prepolymer. S2: 10.8 parts of the precursor, 11.2 parts of glycidyl methacrylate, 0.24 parts of trimethylolpropane triacrylate, 1.4 parts of N,N'-ethylenebisacrylamide and 0.5 parts of N,N'-isophthalenebisacrylamide were mixed, the temperature was raised to 110°C, potassium persulfate was added and the reaction was kept warm for 7.5 hours; S3: after the reaction was completed, the temperature was naturally cooled to room temperature, the product was sieved through a 420-mesh sieve to remove large particles, and then kept warm overnight. After completion, it was sealed and stored to obtain the product.

[0075] Comparative Example 5

[0076] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of the modified resin specifically comprises the following steps, calculated by mass: S1: 4.6 parts of polybutylene succinate diol and 1.5 parts of polycarbonate diol are stirred and mixed uniformly in a high-speed mixer at 55° C. and 200 rpm, the mixture is taken out, added to a reaction container, heated to 85° C., 7.4 parts of diphenylmethane diisocyanate and 0.11 parts of dibutyltin dilaurate are added, and the reaction is kept warm for 4 .5h to obtain the prepolymer; S2: 5.5 parts of the prepolymer, 20.5 parts of glycidyl methacrylate, 0.11 parts of trimethylolpropane triacrylate, 0.5 parts of N,N'-ethylenebisacrylamide and 0.1 parts of N,N'-isophthalenebisacrylamide were mixed, the temperature was raised to 110°C, potassium persulfate was added and the reaction was kept warm for 7.5h; S3: After the reaction was completed, the temperature naturally dropped to room temperature, the product was sieved through a 420-mesh sieve to remove large particles, and then kept warm overnight. After completion, it was sealed and stored to obtain the product.

[0077] Comparative Example 6

[0078] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of modified graphene specifically includes the following steps, calculated by mass: S1: 7.5 parts of functionalized graphene and 0.2 parts of zinc oxide are mixed and added to 90 parts of DMF solution, and then 0.8 parts of succinic anhydride are added and the temperature is raised to 70°C, and the reaction is kept warm for 3 hours. After completion, the product is centrifuged and filtered, and the pretreated solid particles are obtained after drying; S2: 5.3 parts of the pretreated solid particles are irradiated in 120 parts of DMAc solvent by 400W water bath ultrasound for 50mi n, after completion, add 2.3 parts of tetrabutyl titanate, then heat to 55°C and keep ultrasonic for 20 minutes, then add 2.1 parts of 1,4-naphthalenedicarboxylic acid, 0.52 parts of p-aminobenzoic acid and 0.21 parts of 2-methylimidazole, heat to 100°C and keep warm for 4.5 hours; S3: add 0.3 parts of hydrofluoric acid, stir and mix evenly, heat to 120°C and stir at 100 rpm for 15 hours, after the reaction is completed, cool naturally to room temperature, centrifuge and filter, wash with ethanol 3 times and dry in a vacuum drying oven at 80°C for 8 hours.

[0079] Comparative Example 7

[0080] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of modified graphene specifically includes the following steps, calculated by mass: S1: 4.2 parts of functionalized graphene and 0.55 parts of zinc oxide are mixed and added to 80 parts of DMF solution, and then 1.4 parts of succinic anhydride are added and the temperature is raised to 70°C, and the reaction is kept warm for 3 hours. After completion, the product is centrifuged and filtered, and the pretreated solid particles are obtained after drying; S2: 2.6 parts of the pretreated solid particles are mixed in 120 parts of DMAc solvent Ultrasonicate in a 400W water bath for 50 minutes, add 4.2 parts of tetrabutyl titanate, then raise the temperature to 55°C and maintain the temperature for 20 minutes, then add 4.9 parts of 1,4-naphthalenedicarboxylic acid, raise the temperature to 100°C and maintain the temperature for 4.5 hours; S3: add 0.4 parts of hydrofluoric acid, stir and mix evenly, raise the temperature to 120°C and stir at 100 rpm for 15 hours. After the reaction is completed, cool naturally to room temperature, centrifuge and filter, wash 3 times with ethanol, and dry in a vacuum drying oven at 80°C for 8 hours.

[0081] Performance Evaluation

[0082] Mechanical properties: The tensile strength of the composite PE films prepared in the examples and comparative examples was tested with reference to the standard GB / T 1040.3-2008. The test values ​​were recorded in Table 1 as the average of 10 tests.

[0083] Salt spray corrosion resistance test: The composite PE films prepared in the examples and comparative examples were subjected to salt spray corrosion resistance tests. The test environment temperature was 40±2°C, the humidity was 95±2%, the test solution was 5wt% NaCl solution, and the spraying rate was 2mL / 16h·80cm 2 The salt spray corrosion resistance test time is 800h. After the test, observe whether the composite film is damaged, yellowed, cracked or blistering. If so, it is recorded as unqualified, otherwise it is qualified. Each group tests 50 groups of samples, and the qualified rate results are recorded in Table 1.

[0084] Aging resistance test: The composite PE film prepared in the embodiment and the comparative example was prepared into a sample of 1.5cm×1.5cm×0.1cm, placed in a constant temperature and humidity chamber at 68±2℃, 75±3% relative humidity, and stored for 6 months. After 6 months, it was recorded whether the sample had hydrolysis, oxidation, cracking, blistering and damage. If so, it was recorded as unqualified, otherwise it was qualified. 50 samples were tested in each group, and the qualified rate of the samples was recorded and recorded in Table 1.

[0085] Waterproof test: Referring to GB / T 1037-2021, the composite PE films prepared in the embodiments and comparative examples were tested for moisture permeability resistance, and the test values ​​were recorded in Table 1 by taking the average value of 10 tests.

[0086] Table 1 Performance test results

[0087]

[0088] It can be seen from the embodiments and comparative examples of the present application and the data results in Table 1 that embodiments 1 to 3 of the present application have obvious advantages over comparative examples 1 to 7 in terms of mechanical properties, waterproof properties, aging resistance, weather resistance and corrosion resistance. This is mainly due to the combined effect of the modified functional resin, modified graphene and other matching schemes specified in the present application. Comparative examples 1 to 7 did not adopt the technical scheme specified in the present application, resulting in obvious disadvantages in the above-mentioned performance tests. This further proves the necessity of the technical scheme specified in the present application for the technical effect of the present application and solving technical problems.

Claims

1. A composite PE film based on modified graphene, characterized in that: The composite PE film based on modified graphene comprises, by weight, 50-70 parts of polyethylene matrix, 10-20 parts of modified resin, 5-10 parts of modified graphene, 1-1.5 parts of antioxidant, 0.8-1.4 parts of stabilizer, 4-8 parts of plasticizer, 0.5-1 part of lubricant, 2-4 parts of nucleating agent, 1-3 parts of adhesive aid, and 10-15 parts of dispersing solvent; The polyethylene matrix is ​​a composition of high-density polyethylene and linear low-density polyethylene; the mass ratio of the high-density polyethylene to the linear low-density polyethylene is (40-48): (12-20); The preparation method of the modified resin is specifically The following steps are involved: S1: After polybutylene succinate diol and polycarbonate diol are stirred and mixed uniformly at 50-55°C and 200-240rpm in a high-speed mixer, the mixture is taken out, added to a reaction container, heated to 80-85°C, diphenylmethane diisocyanate and dibutyltin dilaurate are added, and the mixture is kept warm for reaction for 4-4.5h to obtain a prepolymer; S2: The prepolymer, glycidyl methacrylate, trimethylolpropane triacrylate, N,N'-ethylenebisacrylamide and N,N'-isophthalenebisacrylamide are mixed, the temperature is raised to 100-120°C, potassium persulfate is added, and the mixture is kept warm for reaction for 6-8h; S3: After the reaction is completed, the temperature is naturally cooled to room temperature, the product is sieved through a 400-450 mesh sieve to remove large particles, and then kept warm overnight. After completion, it is sealed and stored to obtain; The mass ratio of the polybutylene succinate diol, the polycarbonate diol and the diphenylmethane diisocyanate is (4-5): (1-2): (6-8); The mass ratio of the precursor, glycidyl methacrylate, trimethylolpropane triacrylate, N,N'-ethylenebisacrylamide and N,N'-isophthalenebisacrylamide is (4-6):(10-12):(0.2-0.3):(1-1.5):(0.4-0.6).

2. The composite PE film based on modified graphene according to claim 1, characterized in that: The mass ratio of the polyethylene matrix, the modified resin and the modified graphene is (55-65): (12-16): (6-9).

3. The composite PE film based on modified graphene according to claim 2, characterized in that: The mass ratio of the modified graphene, the nucleating agent and the adhesive aid is (6-9): (2.5-3): (1.5-2).

4. The composite PE film based on modified graphene according to claim 3, characterized in that: The preparation method of the modified graphene specifically comprises the following steps: S1: adding the functionalized graphene and zinc oxide to a DMF solution, then adding succinic anhydride and heating to 65-70°C, keeping the temperature for reaction for 2.5-3h, centrifuging and filtering the product after completion, and drying to obtain pretreated solid particles; S2: subjecting the pretreated solid particles to water bath ultrasound at 400-500W for 40-60min in a DMAc solvent, adding tetrabutyl titanate after completion, and then heating to 50-55 ℃, keep warm and ultrasonic for 20-30 minutes, then add 1,4-naphthalene dicarboxylic acid, p-aminobenzoic acid and 2-methylimidazole, heat to 90-100℃ and keep warm for 4-5 hours; S3: add hydrofluoric acid, stir and mix evenly, heat to 110-125℃, stir and react at 80-100rpm for 14-16 hours, after the reaction is completed, cool naturally to room temperature, centrifuge and filter, wash with ethanol 2-3 times, and dry in a vacuum drying oven at 80-85℃ for 6-8 hours to obtain; The mass ratio of the functionalized graphene, zinc oxide and succinic anhydride is (4-4.5): (0.4-0.6): (1.2-1.5); The mass ratio of the pretreated solid particles, tetrabutyl titanate, 1,4-naphthalene dicarboxylic acid, p-aminobenzoic acid and 2-methylimidazole is (5-5.5): (2.2-2.4): (2-2.2): (0.4-0.6): (0.2-0.3).

5. The composite PE film based on modified graphene according to claim 4, characterized in that: The average particle size of the zinc oxide is 10 to 20 nm.

6. The composite PE film based on modified graphene according to claim 5, characterized in that: The antioxidant is at least one of antioxidant 1010, antioxidant 1076, antioxidant B215, antioxidant 168, antioxidant CA and antioxidant 1098.

7. The composite PE film based on modified graphene according to claim 6, characterized in that: The plasticizer is a composition of dioctyl adipate and epoxidized soybean oil; the mass ratio of the dioctyl adipate to the epoxidized soybean oil is (3-5): (1.5-2).

8. The composite PE film based on modified graphene according to claim 7, characterized in that: The nucleating agent is at least one of organic montmorillonite, sorbitol, talcum powder, calcium carbonate and barium sulfate.

9. The composite PE film based on modified graphene according to claim 8, characterized in that: The adhesive auxiliary agent is a composition of maleic anhydride grafted polyethylene and γ-aminopropyltriethoxysilane; the mass ratio of the maleic anhydride grafted polyethylene and γ-aminopropyltriethoxysilane is (4-5): (0.5-1).

10. A method for preparing a composite PE film based on modified graphene according to any one of claims 1 to 9, characterized in that: The specific steps include: S1: adding the modified graphene to a dispersion solvent, and dispersing the modified graphene in a water bath with ultrasonic waves at 400-500W for 60-90min until no agglomeration occurs, to obtain a modified graphene dispersion; S2: pre-mix the modified resin, antioxidant, stabilizer, plasticizer, lubricant, nucleating agent and bonding aid under stirring at a speed of 120-200 rpm, then add the mixture of polyethylene matrix and modified graphene dispersion, stir at a speed of 80-100 rpm until uniform, to obtain a blend; S3: send the blend into a twin-screw extruder for melt blending, the screw speed is 300-400 rpm, the temperature gradient is controlled between 160-200°C to ensure that the material is fully plasticized but not degraded, the extruded melt is formed into a film by a film blowing machine, the blowing ratio is adjusted to (2-3):1, and the film is pulled to the required film thickness and flatness, and then cooled and shaped to complete.

Citation Information

Patent Citations

  • Water-based anti-fouling self-cleaning polyurethane coating with high wear resistance and preparation method thereof

    CN106675370A

  • Thermoplastic polyurethane hot melt adhesive as well as preparation method and application thereof

    CN118813191A